2017
DOI: 10.1016/j.buildenv.2017.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic and exergoeconomic analysis of a non-domestic Passivhaus retrofit

Abstract: This paper presents a thermodynamic and exergoeconomic analysis of a recently-retrofitted Passivhaus non-domestic building. The selected case study, a Community Centre located in London, underwent a deep-energy retrofit in 2011, becoming the first 'non-domestic Passivhaus' retrofit in the country. As the building was retrofitted per Passivhaus standards, which is based solely on First Law analysis, a thermodynamic investigation can provide a novel means by which to assess its exergy efficiency and cost-effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Assuming that thermal comfort is related to a minimum of exergy consumtion, Schweiker and Shukuya [54] compared an exergetic comfort model (human body exergy consumption (HBx-) rate) with the established adaptive comfort model and predicted mean vote (PMV) model, finding a linear relation between adaptive and exergetic model under neutral conditions. A review on the most recent building exergy literature can be found in Hepbasli [55] and García Kerdan et al [56].…”
Section: Building Thermodynamic Analysismentioning
confidence: 99%
“…Assuming that thermal comfort is related to a minimum of exergy consumtion, Schweiker and Shukuya [54] compared an exergetic comfort model (human body exergy consumption (HBx-) rate) with the established adaptive comfort model and predicted mean vote (PMV) model, finding a linear relation between adaptive and exergetic model under neutral conditions. A review on the most recent building exergy literature can be found in Hepbasli [55] and García Kerdan et al [56].…”
Section: Building Thermodynamic Analysismentioning
confidence: 99%
“…Based on this principle, Garcia Kerdan et al developed a comprehensive multi-objective model embedded into the well-known open-source dynamic building energy simulation tool, EnergyPlus [27,28], with the aim to allow for the exergy optimization of possible retrofit strategies for buildings. This model was applied to the retrofit of a three-story non-domestic Passivhaus in the UK [29]; here space heating and DHW were provided by means of a centralized conventional gas boiler and high temperature radiators. The retrofit solution included the installation of a GSHP unit and medium temperature radiators, as well as a mechanical ventilation system with a 90% efficient heat-recovery unit.…”
Section: Exergy Analysis At Building Scalementioning
confidence: 99%